Achieving Business Sustainability Through Financial Literacy And Financial Inclusion In Financial Capital Mediation (A Study On Modern-Based Traditional Markets In Taluk Kuantan) - Ruzikna, Ruzikna; Augustin, Jeneva; Kasmiruddin, Kasmiruddin; Suryalena, Suryalena; Fadli, Mashur (International Journal of Science, Technology & Management, 2025)
Financial literacy enables MSMEs to adopt financial technology, manage risks effectively, and adapt to market changes, increasing their competitiveness in an increasingly competitive market, especially in the digital era. This study aims to measure the influence of financial literacy, financial inclusion, and financial capital on business sustainability in the modern-based traditional market street vendor sector in Kuantan. This study uses a quantitative approach where primary data is collected through surveys and questionnaires from 77 respondents. Partial Least Square (PLS) statistical techniques are used to process the data. The results confirm the significant influence of financial literacy on business sustainability, both directly and indirectly through financial capital. Furthermore, there is an insignificant influence on business sustainability variables through financial capital. Therefore, there is an influence originating from other variables outside the study. The results also show that the intervening variables here have a significant influence on business sustainability variables. Therefore, it can be concluded that the higher the financial literacy of traditional market street vendors, the better the business sustainability will be.